In vitro evaluation of selected medicinal plants for antimicrobial activities against antibiotic resistant clinical bacterial and fungal pathogens - QASIM TURQI KADHIM; HUSSEIN HAMEED ABBAS (International Journal of Pharma and Bio Sciences, 2017)
Dried leaves of Rubia cordifolia, Psidium guajava and Ocimum sanctum obtained from Amrut Kesari, Bangalore, were extracted using methanol as extraction solvent via percolation method at temperature of 50°C. The leaf extracts were tested for antimicrobial activity against clinical isolates of Streptococcus mutans, Streptococcus salivarius, Escherichia coli, Salmonella typhimurium, Aspergillus flavus and Candida albicans using disc diffusion and broth dilution techniques. The leaf extracts of Rubia cordifolia, Psidium guajava, and Ocimum sanctum showed antibacterial activity against the Gram-positive Streptococcus mutans, Streptococcus salivarius and Gram-negative Escherichia coli, Salmonella typhimurium and a remarkable antifungal activity were shown against Candida albicans. P. guajava showed the highest antimicrobial activity (10-20 mm inhibition in diameter) for these microorganisms in the disk diffusion and minimum inhibitory concentration (256-1024µg/ml) assays in comparison with standard ciprofloxacin which showed maximum inhibitory activity(22-35mm inhibition in diameter) in disc diffusion and minimum inhibitory concentration(0.5-1.0µg/ml) assay.